The Impact of Bodily States on Divergent Thinking: Evidence for a Control-Depletion Account - Zhou, Yanyun; Zhang, Yifei; Hommel, Bernhard; Zhang, Hao (Frontiers in Psychology, 2017)
Given previous evidence that bodily states can impact basic cognitive processes, we asked whether such impact can also be demonstrated for creative cognition. In particular, we had participants perform a design improvement task (DIT) and a consequences imagination task (CIT) while standing up, walking in a predetermined pattern, or walking freely. Results show better divergent-thinking performance with unconstrained than with constrained walking, and better performance for walking than for standing. A second experiment assessed performance in an alternative uses task (AUT) and a figural combination task (FCT) while participants were lying, sitting, or standing. Results showed better performance when standing up than when lying or sitting. Taken altogether, these observations provide evidence for an approach in terms of cognitive-control depletion: the more a bodily activity exhausts control resources, the better divergent thinking can unfold, presumably because reduced top-down control brings more ideas into play.